Identification and Characterization of a Glyoxalase I Gene in a Rapeseed Cultivar with Seed Thermotolerance - Yan, Guixin; Lv, Xiaodan; Gao, Guizhen; Li, Feng; Li, Jun; Qiao, Jiangwei; Xu, Kun; Chen, Biyun; Wang, Limin; Xiao, Xin; Wu, Xiaoming (Frontiers in Plant Science, 2016)
Glyoxalase I (GLYI) is a ubiquitous enzyme in all organisms that catalyzes the conversion of the potent cytotoxin methylglyoxal to S-D-lactoylglutathione. Although many reports suggest the importance of GLYI in the plant response to stress, its function in seeds requires further study. Here, we identified a heat-induced GLYI from Brassica napus seeds, BnGLYI, using a comparative proteomics approach. Two-dimensional gel analyses revealed that BnGLYI protein expression upon heat treatment was significantly elevated in thermotolerant seeds but was diminished in heat-sensitive seeds. The BnGLYI-2 and BnGLYI-3 genes from the heat-sensitive and thermotolerant cultivars, respectively, were characterized and analyzed. Only two amino acid residue variations were found between the amino acid sequences of the two genes. Moreover, overexpressing BnGLYI-3 in yeast cells enhanced tolerance to heat and cold stress and significantly increased GLYI activity compared to overexpressing BnGLYI-2. In addition, BnGLYI-3 transformants showed enhanced superoxide dismutase activities under heat and cold treatment, whereas these activities were diminished for BnGLYI-2 transformants. Taken together, these results indicate that overexpression of the BnGLYI-3 gene imparts thermotolerance and cold tolerance in yeast and that the variations in BnGLYI-3 may play an important role in the responses to temperature stresses.